Exploring the bioherbicide and in vitro biofungicide effects of pistachio hulls for their use in sustainable agriculture - Ana I. González-Hernández; Ana M. Vivar-Quintana; Marta I. Saludes-Zanfaño; Victor M. Gabri; M. Remedios Morales-Corts (PLoS ONE, 2026)
Agriculture requires sustainable approaches for effective weed management reducing the negative consequences of synthetic herbicides. In this context, some agricultural by-products such as pistachio hulls could be considered as source of biopesticide compounds due to their allelopathic effect. The application of pistachio hull extract and powder produced an allelopathic effect against the weeds Solanum nigrum , Lactuca serriola and Lolium rigidum in in vitro and in vivo assays. In the in vitro assay, the germination and radicle and epicotyl growth of Lactuca serriola and Solanum nigrum was significantly reduced under both 2.5% and 10% extract concentrations, while in Lolium rigidum the germination was not affected by the 2.5% extract . In pot assay, the effect of the extract (10%) was more noticeable in the broad-leaf weeds Solanum nigrum and Lactuca serriola , while the powder (1 g per pot) seemed to be a more efficient strategy in Lolium rigidum according to the reduction in weeds’ fresh and dry weights and plant number. The allelopathic effects were mainly produced by the high concentration of phenolic compounds such as gallic and protocatequic acids, since the pure compounds application at the concentration found in the extract inhibited seed germination and radicle and epicotyl development. Moreover, hull extract had no biofungicide effect against Alternaria alternata , Botryosphaeria dothidea , Aspergillus niger and Rhizoctonia solani pathogens . Altogether led to conclude that pistachio hull extract and powder could be a good approach to control weeds in sustainable agriculture. Further studies are required to elucidate the mode of action of these phenolic compounds.